Association of Anemia with Postpartum Haemorrhage - Shazia Mahmood Awan, Faiza Khanum, Nabgha Khan Rana, Uzma Afreen, Syed Fazal E Karim Faisal, Shazia Nayyar, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Maternal anaemia is a common condition. According to the World Health Organization, pregnancy anaemia and postpartum anaemia is very frequent across the world, and confers a number of health risks to mother and child. Maternal symptoms and signs include fatigue, paleness and cardiovascular strain, reduced mental and physical performance and increased risk for blood transfusion. Objectives: To determine the association of maternal anaemia with postpartum haemorrhage in pregnant females presenting for antenatal check-up Study Design: Case control study Setting: Department of Obstetrics and Gynaecology B Unit, Mardan Medical Complex. Duration of Study: Study was carried out over a period of six months from 01-08-2019 to 31-01-2020 Subjects and Methods: A total of 224 patients (112 in each group) were included in the study. Cases were females with PPH and controls were females without PPH. Results: Mean age of the patients was 28.0±4.3 and 28.2±5.1 in group-A and B, respectively. Mean gestational age was (38.7±1.8 vs 38.5±2.4), mean BMI was (27.0±4.2 vs 26.2±4.6) and mean Hb was (9.1±2.1 vs 9.9±1.9). Majority of the patients were between para 1-2 in both cases. Anaemia was found in 59 patients (52.7%) of cases and 36 patients (32.2%) of controls (Odds ratio 2.35; 95% CI 1.36 - 4.04). Stratification for age, gestational age, BMI and parity was also carried out. Conclusion: In conclusion, postpartum anaemia has a high prevalence. Anemia during the third trimester of pregnancy, heavy bleeding perceived by the mother during delivery, younger maternal age was associated with postpartum anemia. Keywords: Anaemia, Blood loss, Postpartum haemorrhage